1996
DOI: 10.1159/000164049
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Disease Association with HLA-DQ Antigens in African Americans and Caucasians

Abstract: Previously, we have shown that CD4 levels in African Americans infected with human immunodeficiency virus-1 (HIV-1) were lower than those in Caucasians. To determine whether or not HLA type is associated with susceptibility to HIV-1 infection, we demonstrated serologically that HLA-DQ6(1) and HLA-DQ7(3) were associated with HIV-1 infection in both African Americans and Caucasians. The present investigation was designed to demonstrate whether or not HLA-DQB1 alleles were associated with HIV-1 infection or prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Specific HLA‐DRB1 and HLA‐DQB1 alleles among Afro‐Americans and Caucasians have been shown to be associated with HIV infection (Odum et al. , 1990; Achord et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Specific HLA‐DRB1 and HLA‐DQB1 alleles among Afro‐Americans and Caucasians have been shown to be associated with HIV infection (Odum et al. , 1990; Achord et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular methods identified an association between HLA-DQBl and susceptibility to HIV-1 infection [3]. Based on the epidemiological data, several HLA-DQBl subtypes were found in higher frequency in both African American and Caucasian HIV-l-positive patient popula tions when compared to HIV-1-negative regional controls.…”
Section: Introductionmentioning
confidence: 98%
“…In the Caucasian group, HLA class II antigens associated with HIV-1 infection were identified as HLA-DR10. HLA-DR12 (5), HLA-DQ6 (1) and HLA-DQ7 (3). HLA anti gens demonstrating a possible protective function among African Americans were Cw4 and DR6, whereas Cauca sians expressed none.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HLA class I and II genes were associated with susceptibility or resistance to HIV infection and disease progression . Among the HLA class II molecules, apart from HLA‐DR, specific HLA‐DQB1 and HLA‐DPB1 alleles have been shown to be associated with HIV infection . Flavivirus disease and its association with HLA molecules have been studied .…”
Section: Introductionmentioning
confidence: 99%